2013
DOI: 10.1038/leu.2013.129
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of treatment with imatinib in eosinophilia-associated myeloid/lymphoid neoplasms with PDGFR rearrangements in blast phase

Abstract: treated with vitamin E, which reduced ROS by approximately twofold (Figure 1a). 9,11 Human CD45 þ cells collected from bone marrows and spleens of NSG mice formed colonies in vitro, and vitamin E treatment did not affect the engraftment (Figure 1b). Imatinib-resistant clones carrying either E255K or T315I BCR-ABL1 kinase mutations were detected in three out of five untreated xenografts, but in none of the vitamin E-treated samples (Table 1). In conclusion, we postulate that anti-oxidants such as vitamin E may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 12 publications
2
54
0
3
Order By: Relevance
“…27, [95][96][97] We are aware of several cases in which a fusion gene has only come to attention after patients achieved clearance of blasts or remission of lymphomas with intensive chemotherapy but significant eosinophilia persisted. If performed, molecular analyses have shown that the genetic lesion is usually detectable in granulocytic cells, but also in blasts of myeloid or lymphoid origin, indicating a stem cell disorder with multilineage involvement and a disparate morphologic appearance in BM and lymph nodes.…”
Section: Blast Phase Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…27, [95][96][97] We are aware of several cases in which a fusion gene has only come to attention after patients achieved clearance of blasts or remission of lymphomas with intensive chemotherapy but significant eosinophilia persisted. If performed, molecular analyses have shown that the genetic lesion is usually detectable in granulocytic cells, but also in blasts of myeloid or lymphoid origin, indicating a stem cell disorder with multilineage involvement and a disparate morphologic appearance in BM and lymph nodes.…”
Section: Blast Phase Diseasementioning
confidence: 99%
“…97 Two patients were initially treated with intensive chemotherapy instead of imatinib, but failed to achieve a complete remission; subsequent allogeneic HSCT was shortly followed by relapse within 3 months. 97 The combination of imatinib and intensive chemotherapy, similar to that which has been undertaken with ALL induction regimens such as hyperCVAD in BCR-ABL1-positive ALL, merits further investigation. More data are also needed regarding the role of allogeneic HSCT, given the few numbers of PDGFRA/Bpositive blast phase patients treated to date.…”
Section: Blast Phase Diseasementioning
confidence: 99%
“…The effectiveness of imatinib treatment was also demonstrated in patients with myeloid/lymphoid PDGFR rearrangement in blast phase. Some of them failed prior treatment with intensive chemotherapy and stem cell transplantation and achieved complete hema­tologic response after initiation of imatinib [5]. The concurrent occurrence of lymphoblastic lymphoma with myeloproliferative disorder is not unusual in cases with abnormalities of FGFR1 and PDGFRA , but the association with PDGFRB -rearranged myeloid neoplasms was described only in the last years in few adult cases.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of myeloproliferative disorders with this translocation were described in adults and were sensitive to treatment with the tyrosine kinase inhibitor imatinib. The association of PDGFRB -rearranged myeloid disorder with T-lymphoblastic lymphoma was first described by Chang et al [4] in an adult patient with concurrent acute myeloid leukemia and T-lymphoblastic lymphoma, followed later by several additional reports of adult patients [5-7]. The CCDC88C (formerly reported as KIAA1509 ) gene was first identified as a fusion partner in an adult patient with myeloproliferative disease but with no lymphatic involvement, associated with a t(5; 14)(q33;q32) translocation [8].…”
Section: Introductionmentioning
confidence: 99%
“…These disorders include thrombosis, small vessel vasculitis, systemic lupus erythematosus, autoimmunity, pneumonia, sepsis, and blood transfusion-related acute lung injury. [1][2][3][4] NETs are DNA-based extracellular traps that not only trap and kill invading microbes but also BLOOD, 23 JANUARY 2014 x VOLUME 123, NUMBER 4 CORRESPONDENCE 597…”
mentioning
confidence: 99%